Whole Genome Sequencing of SARS-CoV-2 in Cats and Dogs in South Korea in 2021 - Yeun-Kyung Shin; Oh-Kyu Kwon; Jinhwa Heo; Jinju Nah; Hae-Eun Kang; Yunhee Kang; In Jun Song; Ho-Kyung Sung (Veterinary Sciences, 2022)
SARS-CoV-2 infections have caused unprecedented damage worldwide by affecting humans and various animals. The first reported animal infection was observed in a pet dog in Hong Kong in March 2020. 36 countries reported 692 SARS-CoV-2 infections in 25 different animal species by 31 August 2022. Most outbreaks were caused by contact with SARS-CoV-2 infected humans. In South Korea, the first SARS-CoV-2 infection in an animal was reported in a cat in February 2021. As of 31 December 2021, 74 dogs and 42 cats have been confirmed to have SARS-CoV-2 in South Korea. Here, we identified various SARS-CoV-2 genomic lineages in SARS-CoV-2 confirmed cats and dogs. Among the 40 animal samples sequenced for lineage identification, a total of eight Pango lineages (B.1.1.7 (Alpha variant), B.1.429 (Epsilon variant), B.1.470, B.1.497, B.1.619.1, B.1.620, AY.69 (Delta variant), and AY.122.5 (Delta variant)) were identified. The dominant lineages were AY.69 (Delta variant; 37.5%), B.1.497 (35.0%), and B.1.619.1 (12.5%). This study provides the first reported cases of six lineages (B.1.470, B.1.497, B.1.620, B.1.619.1, AY.69 (Delta variant)), and AY.122.5 (Delta variant) in cats and dogs. Our results emphasize the importance of monitoring SARS-CoV-2 in pets because they are dynamic hosts of variant Pango lineages of SARS-CoV-2.